Not Frail and Elderly: How Invasive Can We Go in This Different Type of Adult Spinal Deformity Patient?. Issue 22 (15th November 2021) - Passias, Peter G.; Pierce, Katherine E.; Passfall, Lara; Adenwalla, Ammar; Naessig, Sara; Ahmad, Waleed; Krol, Oscar; Kummer, Nicholas A.; O'Malley, Nicholas; Maglaras, Constance; O'Connell, Brooke; Vira, Shaleen; et al.
Abstract : Frailty status impacted the balance of surgical invasiveness relative to operative risk in an inverse manner. The opposite was seen amongst elderly patients with frailty status less than their chronologic age. Surgeons should consider incorporation of frailty status over age status when determining realignment plans in patients of advanced age. Abstract : Study Design: Retrospective review of a single-center spine database. Objective: Investigate the intersections of chronological age and physiological age via frailty to determine the influence of surgical invasiveness on patient outcomes Summary of Background Data: Frailty is a well-established factor in preoperative risk stratification and prediction of postoperative outcomes. The surgical profile of operative patients with adult spinal deformity (ASD) who present as elderly and not frail (NF) has yet to be investigated. Our aim was to examine the surgical profile and outcomes of patients with ASD who were NF and elderly. Methods: Patients with ASD 18 years or older, four or greater levels fused, with baseline (BL) and follow-up data were included. Patients were categorized by ASD frailty index: NF, Frail (F), severely frail (SF]. An elderly patient was defined as 70 years or older. Patients were grouped into NF/elderly and F/elderly. SRS-Schwab modifiers were assessed at BL and 1 year (0, +, ++). Logistic regression analysis assessed the relationship between increasing invasiveness, no reoperations, or major complications, and improvement in SRS-Schwab modifiers [Good Outcome]. Decision tree analysis assessed thresholds for an invasiveness risk/benefit cutoff point. Results: A total of 598 patients with ASD included (55.3 yr, 59.7% F, 28.3 kg/m 2 ). 29.8% of patients were older than 70 years. At BL, 51.3% of patients were NF, 37.5% F, and 11.2% SF. Sixty-sis (11%) patients were NF and elderly. About 24.2% of NF-elderly patients improved in SRS-Schwab by 1 year and had no reoperation or complication postoperatively. Binary regression analysis found a relationship between worsening SRS-Schwab, postop complication, and reoperation with invasiveness score (odds ratio: 1.056 [1.01–1.102], P  = 0.011). Risk/benefit cut-off was 10 ( P  = 0.004). Patients below this threshold were 7.9 (2.2–28.4) times more likely to have a Good Outcome. 156 patients were elderly and F/SF with 16.7% having good outcome, with a risk/benefit cut-off point of less than 8 (4.4 [2.2–9.0], P  < 0.001). Conclusion: Frailty status impacted the balance of surgical invasiveness relative to operative risk in an inverse manner, whereas the opposite was seen amongst elderly patients with a frailty status less than their chronologic age. Surgeons should perhaps consider incorporation of frailty status over age status when determining realignment plans in patients of advanced age. Level of Evidence: 3